Analisis Usaha Totebag Custom Ramah Lingkungan sebagai Solusi Inovatif untuk Mengurangi Sampah Plastik - Ari Dian Prastyo; Glorian Hilarius Kiantin Beda; Fikri Saputra; Wien Kuntari (International Forum of Researchers and Lecturers, 2025)
The issue of plastic waste has become a global environmental challenge, with Indonesia being one of the largest contributors. This study aims to analyze the business opportunity of eco-friendly custom tote bags as an innovative solution to reduce plastic waste in society. The research adopts the Business Model Canvas (BMC) framework to design strategies for a business that encompasses nine key elements. Findings reveal that custom tote bags made from eco-friendly materials such as muslin and canvas offer added value through personalized designs, effective digital marketing, and market segmentation targeting environmentally conscious youth. This study provides guidance for entrepreneurs to capitalize on the market potential of eco-friendly products and suggests optimizing social media for marketing efforts.